Evaluation of Fungicides and Antibiotics Against Pestalotiopsis Funerea in Vitro Causing Leaf Spot of Eucalyptus globulus - Upadhyay, Rajeev K. (Indian Forester, 1984)
Effect of various fungicide and antibioties on the growth of Pestulotiopsis funerea Desm. causing leaf spot of Eucalyptus globulus Labill was studied. Amongest the fungicides, phygon XL was found to be most ffective followed in order by difultan 80 W, diathane Z78, zincop and copramar. All of them exhibited loss in their inhibition value on succsive prolongation of incubation at lower concentrations except difoltan. Out of the five antihlotlcs used, mycostatin proved to be most detrimenal followede by streptopenicilin griseofulvin, streptomycin sulphate and benzyl penicillin.